Age differences in Exposure and Reactivity to Interpersonal Tensions among Black and White Individuals across Adulthood - Birditt, Kira S. (2011)
The present study examined age differences in exposure and reactivity to interpersonal tensions among White and Black Americans. Participants from the National Study of Daily Experiences II (NSDE II, n= 1696 White and n = 239 Black; ages 34 to 84) reported their experiences of daily interpersonal tensions and well-being (positive and negative affect) over 8 days and provided salivary cortisol samples. A total of 40% of respondents reported having an argument and 62% reported avoiding an argument. Multilevel models estimated separately for Black and White respondents revealed that older people reported fewer interpersonal tensions (i.e., less exposure) than did younger people. However, age differences in reactivity to tensions (e.g., appraisals, coping strategies, implications of tensions for affect and cortisol) varied by race. Although older Black respondents reported tensions were less stressful than younger Black respondents, there were fewer age difference in reactivity to tensions overall among Black respondents compared to White respondents. Findings are consistent with the exposure reactivity model and gerontological theories of emotion regulation but show that the specific age differences vary by race which may indicate unique strengths and vulnerabilities among Whites and Blacks.